RANCANG BANGUN SISTEM MONITORING DENGAN VIDEO STREAMING DAN RECORDING SEBAGAI PEMANTAU RUANGAN KELAS MENGGUNAKAN WEBCAM BERBASIS OPENWRT - Aris Sarwono (MEDIA ELEKTRIKA, 2019)
Network Monitoring Sistem is a collection of systems that have a function to observe or monitor systems that allow for errors in the system till it can be detected. Technological advances create a monitoring system using the Closed Circuit Television. Utilization of this device can make it easier to monitor the situation or condition of a room, so as to prevent the occurrence of a crime. This research use software system design that aims to facilitate the translation of system requirements that will be built or developed to estimate the system created is a quality system. Encoding on this system is the result of system design that will be implemented by using PHP, Html and bash script. And the last is a system reliability test before the system can actually be implemented through testing every function of the system that has been designed, and system feasibility testing. The results show that the design of monitoring system run well according to its function which is able to give info of the condition of a room in real time, can run according to the school's need for monitoring and supervision, as well as what options are given to monitor the space that is efficient and practical.